USE OF PROGRAMMING ENVIRONMENT IN TEACHING INFORMATION TECHNOLOGIES AND INFORMATICS SECONDARY EDUCATIONAL SCHOOLS - Nayimovich, Zaripov Nozimbek (International Journal of Psychosocial Rehabilitation, 2020)
The use of teaching methods in teaching programming languages in secondary schools enhances student engagement, motivates independent research and improves educational performance.